2002
DOI: 10.1557/proc-744-m7.2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AlInAsSb and AlGaInAsSb MBE-grown Digital Alloys

Abstract: As one of the few Type I band offset, antimony-based material systems available for 3.3 to 4.2 micron mid-infrared multiple quantum well lasers, AlInAsSb alloys have been used as barriers with InAsSb wells. Previously, AlxIn(1-x)AsySb(1-y) quaternary alloys have been grown by MBE as random alloys up to an aluminum fraction, x = 0.10 on GaSb substrates and x = 0.15 on InAs substrates. Random alloy growth of quaternary films with increased aluminum content, although beneficial to the devices, is limited by a mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…V C 2016 AIP Publishing LLC 108, 081102-1 of the resulting Al x In 1Àx As y Sb 1Ày digital alloy films are provided elsewhere. [18][19][20] A cross-sectional schematic of the Al 0.7 In 0.3 As 0.3 Sb 0.7 device is shown in Fig. 1.…”
mentioning
confidence: 99%
“…V C 2016 AIP Publishing LLC 108, 081102-1 of the resulting Al x In 1Àx As y Sb 1Ày digital alloy films are provided elsewhere. [18][19][20] A cross-sectional schematic of the Al 0.7 In 0.3 As 0.3 Sb 0.7 device is shown in Fig. 1.…”
mentioning
confidence: 99%
“…Zederbauer et al have improved AlInAsSb random alloy growth on InAs, which exhibits similar challenges to growth on GaSb. Most pertinent to the work described here, though, Vaughn et al have recently shown that stable AlInAsSb can be grown well within the miscibility gap by molecular beam epitaxy (MBE) as a digital alloy of the component binaries, AlAs, AlSb, InAs, and InSb. Using this approach, mid-IR InAsSb/AlInAsSb type-I diode lasers have previously been demonstrated. , However, these previous studies were limited to Al fractions ranging from 0% to 40%, and photoluminescence (PL) was only observed up to Al fractions of 30%. In this letter, we report on the growth and optoelectronic properties of AlInAsSb digital alloys with Al fractions ranging from 0% to 80%; we identify the functional dependence of the direct bandgap and band offsets on the Al fraction, as well as a probable transition from direct-gap to indirect-gap at an Al fraction of ∼72%.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the increased understanding of surfactant mediated growth, the effect of growth temperature, and the ability to control material deposition on the sub-monolayer scale have allowed for high-quality digital alloy growth. [43][44][45] These advances suggest the potential for deterministically designing APD materials on the few atom scale, the results of which will be discussed later in this paper.…”
mentioning
confidence: 99%